Wildlife anatomy : the curious lives & features of wild animals around the world - Rothman, Julia; Hiley, Lisa (Rothman, Julia. Anatomy series., 2023)
"In Wildlife Anatomy, the latest entry in Julia Rothman's series of Anatomy books, Rothman captures the excitement and distinctive attributes of wild animals around the world. The book is packed with hundreds of her charming, original illustrations, detailing the unique features of animals of the rainforest, desert, grasslands, oceans, and much more. From lions, bears, and zebras to monkeys, mongoose, bats, elephants, giraffes, hippos, and much more, Rothman's visual guide covers all the key features, right down to the anatomy of a lion's claw and a wild horse's hoof"--